2022
DOI: 10.1155/2022/4806982
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Disorders of Cattle in the Tole District of Southwest Ethiopia and Their Prevalence and Associated Risk Factors

Abstract: Reproduction is a basic requirement for efficient cattle production to continue or cease; whereas, reproductive disorders are the leading cause of economic loss in the cattle industry. To determine the prevalence and associated risk factors of major reproductive disorders in cattle in the Tole district, a cross-sectional study design was conducted from October, 2020, to October, 2021. To identify potential risk factors for cattle reproductive disorders, a multivariable random effect logistic regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Furthermore, the incidence of retention of placenta was found to be the highest (18.36%) among the various categories of reproductive disorders in our study. This finding is consistent with the results of previous studies that have highlighted the significance of placental retention as a major reproductive disorder (Jeong et al, 2018; Tulu & Negera, 2022). Similarly, repeat breeding (11.19%) and metritis (6.27%) also contributed significantly to the overall incidence of reproductive disorders in our resource population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the incidence of retention of placenta was found to be the highest (18.36%) among the various categories of reproductive disorders in our study. This finding is consistent with the results of previous studies that have highlighted the significance of placental retention as a major reproductive disorder (Jeong et al, 2018; Tulu & Negera, 2022). Similarly, repeat breeding (11.19%) and metritis (6.27%) also contributed significantly to the overall incidence of reproductive disorders in our resource population.…”
Section: Discussionsupporting
confidence: 93%
“…Reproductive disorders in dairy cattle are influenced by various factors, including inadequate nutrition, poor reproductive management practices, infectious diseases, environmental stressors and genetic predisposition (Dereje et al, 2018; Duguma, 2022; Tulu & Negera, 2022; Yadav et al, 2023). The genetic component has a relatively smaller impact on determining the occurrence of these disorders compared to other factors, such as environmental influences, due to the low heritability of the trait.…”
Section: Introductionmentioning
confidence: 99%
“…These results are more or less similar to the present study. In addition, Tulu et al (2022) observed the three main reproductive disorders in their studied areas and the incidence rates were abortion (17.8%), stillbirth (4.8%), and dystocia (3.3%). Yohannes and Alemu (2019) reported that Dystocia, repeat breeder, retained fetal membrane, abortion; metritis, anestrous and uterine and vaginal prolapse were recorded with prevalence of 15.5, 8.1, 5.3, 4.5, 2.6, 2.3 and 1.0%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…In Ethiopia, dairy farming faces substantial challenges due to reproductive diseases, resulting in economic losses and subpar reproductive outcomes in smallholder dairy farms [ 4 , 5 ]. Reproductive disorders such as abortion, dystocia, stillbirth, retained fetal membrane, endometritis, and pyometra are prevalent [ 6 , 7 ]. Several of these disorders stem from genital infections, some of which may have zoonotic potential [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%